THE RECORD OF MIOCENE IMPACTS IN THE ARGENTINE PAMPAS - Schultz P.H.; Harris R.S.; Zárate M.; Hames W.E.; Bunch T.E.; Wittke J.; Koeberl C.; Renne P. (My University, 2006)
Argentine Pampean sediments represent a nearly continuous record of deposition since the late Miocene (~ 10 Ma). Previous studies described five localized concentrations of vesicular impact glasses from the Holocene to late Pliocene. Two more occurrences from the late Miocene are reported here: one near Chasicó (CH) with an 40Ar/39Ar age of 9.24 ± 0.09 Ma, and the other near Bahía Blanca (BB) with an age of 5.28 ± 0.04 Ma. In contrast with andesitic and dacitic impact glasses from other localities in the Pampas, the CH and BB glasses are more mafic. They also exhibit higher degrees of melting with relatively few xenoycrysts but extensive quench crystals. In addition to evidence for extreme heating (>1700 °C), shock features are observed (e.g., planar deformation features [PDFs] and diaplectic quartz and feldspar) in impact glasses from both deposits. Geochemical analyses reveal unusually high levels of Ba (~7700 ppm) in some samples, which is consistent with an interpretation that these impacts excavated marine sequences known to be at depth. These two new impact glass occurrences raise to seven the number of late Cenozoic impacts for which there is evidence preserved in the Pampean sediments. This seemingly high number of significant impacts over a 106 km2 area in a time span of 10 Myr is consistent with the number of bolides larger than 100 m in expected to enter the atmosphere but is contrary to calculated survival rates following atmospheric disruption. The Pampean record suggests, therefore, that either atmospheric entry models need to be reconsidered or that the Earth has received an enhanced flux of impactors during portions of the late Cenozoic. Evidence for the resulting collisions may be best preserved and revealed in rare dissected regions of continuous, low-energy deposition such as the Pampas. Additionally, the rare earth element (REE) concentrations of the target sediments and impact melts associated with the Chasicó event resemble the HNa/K australites of similar age. This suggests the possibility that those enigmatic tektites could have originated as high-angle, distal ejecta from an impact in Argentina, thereby accounting for their rarity and notable chemical and physical differences from other Australasian impact glasses. © The Meteoritical Society, 2006.
Keywords: Holocene; Pliocene; Miocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен